Nature-Based School for Strengthening Islamic Character Education: A Case Study from Indonesia - Karadona, Rosika Indri; Rahmawati; Ismail; Sari, Arni Puspita (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2025)
This research aims to comprehensively review the background, concepts and benefits of implementing the Natural School curriculum based on Islamic Character Education in forming better and more resilient individuals in facing the dynamics of the times. This research uses a qualitative case study-type approach with research techniques and instruments in the form of observation, documentation and interviews. The subjects of this research are school principals, teachers, students and parents. Fourteen sources provided information about the implementation of the curriculum and the programs that had been implemented. The data analysis technique was conducted through descriptive analysis prepared using primary and secondary data. This research shows that the application of the Natural School lies in a natural approach that leads to learning in an open environment. Children are invited to learn through direct observation, exploration and experimentation with nature, helping them understand the close relationship between humans and nature while fostering a sense of love and responsibility for the environment. Islamic character education is a key element where values ​​such as honesty, fairness, discipline and responsibility, understanding and applying Islamic teachings in daily life, habituation to worship and religious activities are integrated through various learning activities.